Strategi brand indomie dalam membangun identitas nasional melalui produk makanan kreatif - fathoni, achmad fahrul (Maliki Interdisciplinary Journal, 2025)
Indomie is not merely an instant noodle brand but has evolved into a symbol of Indonesia’s national identity, recognized globally. This study aims to analyze Indomie’s branding strategies in promoting local cultural values on a global stage through a glocalization approach. Using a descriptive qualitative method, the research reveals that Indomie’s success as a cultural icon stems from product innovations inspired by traditional Indonesian flavors, packaging that reflects cultural richness, and communication strategies tailored to both local and international markets. Glocalization plays a pivotal role in Indomie’s branding, allowing the brand to cater to local tastes while preserving national identity amidst globalization. The findings suggest that culturally-driven branding strategies can serve as effective tools of diplomacy and reinforce brand positioning in global markets.